Hack/slash omnibus. Stefano Caselli ... [et al.]]. - Seeley, Tim (Image Comics, 2010)
In almost every slasher movie, there's one girl who makes it all the way to the end. She's the survivor-- the last girl. Meet Cassie Hack, the lone survivor of an attack by the vicious slasher known as the Lunch Lady. Now Cassie and her monstrous partner Vlad travel the country, hunting down and killing other slashers before they can leave a trail of blood and terror.